1988
DOI: 10.3758/bf03337671
|View full text |Cite
|
Sign up to set email alerts
|

Education and the selection task

Abstract: The present study was concerned with the effects of education level and area of expertise on performance on the standard abstract selection task. Subjects had received bachelor's or doctoral degrees. Contrary to some recent results reported by Hoch and Tschirgi (1985), no effect of education level was found. However , there was a significant effect for area of expertise. Subjects trained in mathematics performed better than subjects from computer science, electrical engineering, and the social sciences. An exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
3
13
0
Order By: Relevance
“…3 This finding is similar to that of Jackson and Griggs (1988) who found a mathematical group of solvers performed significantly better on the abstract Wason Selection Task than subjects with other areas of specialism. Though negative conclusion bias is not entirely absent, it hardly seems a major factor here.…”
Section: Discussionsupporting
confidence: 77%
“…3 This finding is similar to that of Jackson and Griggs (1988) who found a mathematical group of solvers performed significantly better on the abstract Wason Selection Task than subjects with other areas of specialism. Though negative conclusion bias is not entirely absent, it hardly seems a major factor here.…”
Section: Discussionsupporting
confidence: 77%
“…We assume that the minority of subjects who consistently give the correct answer in all versions of the task use this meta-inferential approach. As one might expect, the size of this minority is affected by the level of formallogical competence of the population tested (Gigerenzer & Hug, 1992;Hoch & Tschirgi, 1985;Jackson & Griggs, 1988;Lehman & Nisbett, 1990). Some experiments have aimed at increasing the size of this minority by encouraging a more reflective stance (Cheng, Holyoak, Nisbett, & Oliver 1986;Hoch & Tschirgi, 1985;Johnson-Laird & Wason, 1970a;Platt & Griggs, 1993;Wason, 1969).…”
Section: Spontaneous Inference and Reflective Meta-inferencementioning
confidence: 99%
“…Finally, Table 1 gives an indication of the errors made by subjects. Previous research Jackson and Griggs, 1988;Wason, 1966) has found that many subjects choose only P or both P and Q. These patterns of incorrect responses are also prevalent in the selections tasks used in this experiment.…”
Section: Resultsmentioning
confidence: 69%